ANALISIS YURIDIS TERHADAP PERKARA NO.363/Pid.Sus/2020/PN Sdn TENTANG PELECEHAN SEKSUAL ANAK DIBAWAH UMUR DI PENGADILAN NEGERI SUKADANA LAMPUNG TIMUR - Jefri Ari Putra (Muhammadiyah Law Review Journal, 2022)
The main problem of this research is about Legal Protection Against Victims of Sexual Harassment with Child Victims. In the case of Legal Protection for Victims of Sexual Harassment with Child Victims, it is contained in Law Number 23 of 2002 concerning Child Protection Article 81 Paragraph (2). In the realization of Legal Protection Against Victims of Sexual Harassment with Victims of Minors, for this reason the study has 2 (two) problem formulations, namely (1) How is legal protection for victims of sexual harassment with victims of minors (2) What are the factors that cause abuse sex with minors.This research method uses an empirical juridical approach which is carried out by interviewing several respondents or competent sources who are directly related to the writing of this thesis, in order to obtain operational data for empirical research conducted through field research.The results of this study prove that legal protection for victims of child sexual abuse has been carried out properly and fairly through Case Number: 363/Pid.Sus/2020/PN.Sdn on behalf of Bayu Samudra Als Juanto Bin Marsudi at the Sukadana District Court. well, with the prosecutor's demands, namely imprisonment for 10 (ten) years and a fine of Rp. 500,000,000 - (five hundred million rupiah) subsidiary to imprisonment for 5 (five) years to the defendant with all the evidence presented before the trial and the judge's considerations regarding aggravating and mitigating matters, namely his actions destroying the child's future, giving trauma and mitigating things The defendant behaves politely before the trial and regrets his actions. But to prevent abuse of children, both as victims and perpetrators, it is necessary to socialize children during their development period.